Effect of treatment of gestational diabetes mellitus: A systematic review and meta-analysis - Nalinee Poolsup (2018)
Objective: To assess the efficacy and safety of treating pregnant women with gestational diabetes mellitus in comparison to usual antenatal care. Methods: A systematic review and meta-analysis was conducted by including randomized controlled trials comparing any form of therapeutic intervention in comparison to usual antenatal care. A literature search was conducted using electronic databases together with a hand search of relevant journals and conference proceedings. Results: Ten studies involving 3,881 patients contributed to meta-analysis. Our results indicated that gestational diabetes mellitus treatment significantly reduced the risk for macrosomia (RR, 0.47; 95% CI, 0.38-0.57), large for gestational age births (RR, 0.55; 95% CI, 0.45-0.67), shoulder dystocia (RR, 0.42; 95% CI, 0.23-0.77) and gestational hypertension (RR, 0.68; 95% CI, 0.53-0.87) without causing any significant increase in the risk for small for gestational age babies. However, no significant difference was observed between the two groups regarding perinatal/neonatal mortality, neonatal hypoglycemia, birth trauma, preterm births, pre-eclampsia, caesarean section and labor induction. Conclusion: Treating GDM reduces risk for many important adverse pregnancy outcomes and its association with any harm seems unlikely. © 2014 Poolsup et al.